Relationships between vegetation of Macedonian pine (Pinus peuce Griseb.) and different types of soils on which it develops - Mandžukovski, Dejan; Teofilovski, Aco; Andreevski, Marjan; Ćušterevska, Renata; Tzonev, Rossen; Dimitrov, Marius (Walter de Gruyter GmbH, 2022)
Abstract This paper deals with relationships between vegetation of Macedonian pine (Pinus peuce) and soils developed on different parent materials on the territory of North Macedonia. We analysed the floristic composition at localities on limestone, on scree of dolomite marble and on scree of silicate. On limestone and scree of dolomite marble, rendzinas on hard limestone and dolomite have developed, and on silicate parent material brown forest soils. The vegetation was sampled according to the Braun-Blanquet approach. DCA and indicator values were used for ecological interpretation of the vegetation patterns. The mechanical and chemical properties of soil and textural classes were also processed. An evident increased presence of carbonates in the soil of scree of dolomite marble on Nidže Mountain was observed, unlike that on Shar Mountain which has formed on typical limestone. Although it is a forest community dominated by the same species, differences between the massifs, the precipitation regime, geology, differences in soil properties in relation to the appearance of carbonates and pH values, and other factors, result in differences in their floristic composition and are the reason for the distinction between the two groups. On silicate on Nidže Mountain, Macedonian pine forests have also developed on brown forest soils, with a different floristic composition to that of the other group on carbonate (dolomite and limestone).